Performance Analysis of Driving Moment of U- type Slide Constrained Chain Conveyor - Yin Ruihua; Hong Lin (Jixie chuandong)
In view of the U- type slide constrained chain conveyor,the impact of the load gravity under the extreme position is analyzed. The position which the chain carries a different number of load and the chain moves to different positions may make different results. By using the method of moment and with the help of MATLAB,the change of pin shaft bearing is calculated. Then the limiting cases of the chain pin shaft under the gravity load are got. According to the analysis of the pin shaft stress and the driving moment features,the location where the maximum driving moment appears and the size of the reaction are got. It provides a basis for the type of driving and device selection. At the same time,it provides data base for related structural strength design of conveying equipment.